(untitled) (Bangladesh Journal of Pharmacology, 2015)
Cabozantinib is a tyrosine kinase inhibitor involved in inhibition of cell proliferation and colony formation. We studied anti-cancer properties of cabozantinib in oral squamous cell carcinoma cells. The viability of BHY and HSC-3 cells decreased with increase in cabozantinib concentration and time. The proliferation of cell lines was affected by increasing concentration of cabozantinib from 0.3 to 1.2 ?M after 48 hours of treatment. The expression of MET and phosphorylated MET was not affected by cabozantinib treatment. Cabozantinib-treated cells when compared to control, showed concentration-dependent increase in BHY and HSC-3 cells during G2/M phase and decrease in S phase with increase in cabozantinib concentration. Annexin-V/propidium iodide double staining showed that cells with annexin-V increased with the increase in cabozantinib concentration. The expression of apoptosis related proteins cleaved caspase-3 and cleaved-PARP were increased with increase in cabozantinib concentration. It was also found that suppression of FAK activation and expression was dose dependent. The results from this study revealed that cabozantinib can be useful in developing a drug for effective treatment of oral squamous cell carcinoma cells.